A long and thorny road: Regulatory cooperation under the framework for advancing transatlantic economic integration - Stormy Mildner; Oliver Ziegler (Intereconomics, 2009)
When the European Union and the United States agreed on the Framework for Advancing Transatlantic Economic Integration at the EU-US Summit on 30 April 2007, creating the Transatlantic Economic Council (TEC), they praised themselves for opening a new era in transatlantic regulatory cooperation. Transatlantic integration and growth were said to be enhanced and efforts to reduce barriers to transatlantic trade and investment redoubled. However, after two meetings of the TEC with only modest achievements, enthusiasm has faded quickly and finger pointing has begun anew. What went wrong?
Keywords: 330